2015
DOI: 10.5539/gjhs.v8n5p134
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into Shelf Life of Fresh Dates and Pistachios in a Package Modified With Nano-Silver

Abstract: Aims:The aim of this study was to apply polymer films containing silver nanoparticles as a new method for increasing the shelf life and preserving the quality of export/commercial products of Kerman Province and determine the ideal temperature for preserving these products.Methods:After preparing nano-composite films containing silver nanoparticles (3% and 5% by weight), Mazafati dates were packed in them and stored with their control samples under four temperatures. In the second series, the films were filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Oxidation, microbial invasion, and metabolism are the main factors causing deterioration of foods and fruits during production, transportation, and storage [170]. Nowadays, AgNPs, silver nitrate and nanoclay are commonly used in the food packaging industry to resist microbial contamination and to improve barrier properties, thus prolonging shelf life and freshness of packaged foods and drinks [171,172,173,174]. As mentioned previously, colloidal nanosilver and silver nitrate have been used for more than 100 years in the United States [32].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Oxidation, microbial invasion, and metabolism are the main factors causing deterioration of foods and fruits during production, transportation, and storage [170]. Nowadays, AgNPs, silver nitrate and nanoclay are commonly used in the food packaging industry to resist microbial contamination and to improve barrier properties, thus prolonging shelf life and freshness of packaged foods and drinks [171,172,173,174]. As mentioned previously, colloidal nanosilver and silver nitrate have been used for more than 100 years in the United States [32].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Mousavi et al . ( 2016 ) showed antioxidant properties of 3 and 5% nano-silver packaging and their beneficial effect on sensory and organoleptic quality of Mazafati date within 53 days of storage and also showed that the use of nanoparticles causes fixed physical features including color of fresh pistachio )Mousavi et al ., 2016). The shelf life of nuts in different groups was determined based on the before-mentioned microbial and chemical analysis.…”
Section: Discussionmentioning
confidence: 98%
“…( 2016 ) investigated effect of nano-silver packaging on shelf life of packaged saffron and found that adding 4000 ppm nano-silver in the packing causes mold count to decrease to 4 log during 6 months (Eslami et al ., 2016 ); these results are consistent with those of ours which showed an average 3 log reduction in mold count in most groups when 3% nano-silver was used. Furthermore, by decreasing mold count in treated samples, aflatoxin was not found in none of them in our study which is consistent with a previous study (Mousavi et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies of Agenabled containers found no or a very modest (2 days or less) increase in the edible lifetime of pork shoulder or chicken fillets (Azlin-Hasim et al 2015;Kernberger-Fischer et al 2017). Some of the studies did find fairly significant (greater than 2 days) extensions of the lifetime of the stored food, while others indicated a significant increase but did not provide all the necessary information to fully understand the implications (Emamifar et al 2010;Yang et al 2010;Jiang et al 2013;Metak and Ajaal 2013;Motlagh et al 2013;Cozmuta et al 2015;Donglu et al 2016;Mousavi et al 2016;Li et al 2017;Tavakoli et al 2017). These findings suggest that there is not a consensus as to whether Ag-enabled food storage containers are an effective method for reducing food spoilage and extending the lifetime of stored food.…”
Section: Novel Food Packagingmentioning
confidence: 99%